Faktor-Faktor yang Berhubungan dengan Motivasi Kerja Pegawai Tetap di Rumah Sakit Umum Daerah Kabupaten Penajam Paser Utara Kalimantan Timur Tahun 2014 - Damayanti, Sisvana (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
The study aims to determine the relationship between the characteristics of a permanent employee, factors satisfiers and dissatisfiers factors on employee motivation remains in District General Hospital North Penajam Paser. The study was conducted in May and June 2014 using a questionnaire with closed questions. Analyses were performed quantitative approach with a cross-sectional study design. The sample of the study was 138 from 181 people of the total population. The results of this study indicate that as many as 57,2% of respondents have less motivation to work better, and 42,8% of respondents have a good motivation to work, as well as the most dominant variable with a variable work motivation is job security. Hospitals are advised to have a specific policy about job security as permanent employees holding shuttle transportation employees, routine health check and calibrate its permanent employee health equipment in the District General Hospital North Penajam Paser.